Hoards, grave goods, jewellery : objects in hoards and in burial contexts during the Mongol invasion of Central-Eastern Europe - Vargha, Mária (Archaeopress archaeology., 2015)
"This monograph examines one specific hoard horizon, which is connected to the Mongol invasion of Hungary (1241-42). With this catastrophic event, the historical context is both well-known and much discussed by contemporaries and modern scholars. This opportunity to examine material connected to a sole event, but across a broad spectrum of geographical space and social class, is unique for hoard horizons in Hungary, and, for that matter, in Europe. Though this study focuses on hoards connected to the Mongol invasion, it is also relevant beyond this specific context. The work addresses issues concerning hoard finds and material culture, and examines how finds are related when found in different contexts (a hoard, grave, or settlement feature), thus the questions raised and conclusions reached are important for other medieval hoard finds. By comparing hoards related to a single historical event to a contemporaneous site - containing a village, a church, and a cemetery - assessments can be made regarding how hoards reflect social issues such as stratification, wealth, status, and fashion."--